Active labor market policy effects for women in Europe: A survey - Annette Bergemann; Gerard van den Berg (Institute for Labour Market Policy Evaluation (IFAU), 2007)
We survey the recent literature on the effects of active labor market policies on individual labor market outcomes like employment and income, for adult female individuals without work in European countries. We consider skill-training programs, monitoring and sanctions, job search assistance, and employment subsidies. The results are remarkably uniform across studies. We relate the results to the relevant level of female labor force participation.
Keywords: J64; 330; Job search; female labor supply; wages; unemployment; schooling; training; monitoring; participation; Arbeitsmarktpolitik; Weibliche Arbeitskräfte; Arbeitslosigkeit; Einkommen; Europa